2017
DOI: 10.1371/journal.pone.0185429
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of mutations mediated by CRISPR/Cas9 in the hairy root transformation system of Brassica carinata

Abstract: A protocol for the induction of site-directed deletions and insertions in the genome of Brassica carinata with CRISPR is described. The construct containing the Cas9 nuclease and the guide RNA (gRNA) was delivered by the hairy root transformation technique, and a successful transformation was monitored by GFP fluorescence. PAGE analysis of an amplified region, presumably containing the deletions and insertions, demonstrated up to seven different indels in one transgenic root and in all analyzed roots a wildtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…Aspergillus niger, cellulase (Srivastava et al, 2016) gene involved in HRs architecture (BcFLA1) in Brassica carinata (Kirchner et al, 2017). The possibility to generate HR clones harboring knock-out gene(s) will facilitate metabolic pathway understanding or modification.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Aspergillus niger, cellulase (Srivastava et al, 2016) gene involved in HRs architecture (BcFLA1) in Brassica carinata (Kirchner et al, 2017). The possibility to generate HR clones harboring knock-out gene(s) will facilitate metabolic pathway understanding or modification.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Plant cultivation and screening for transgenic roots was done as described in Kirchner et al (2017) for the CRISPR experiments. As many 2-cm root tips as possible were harvested from each transgenic root for expression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This is further supported by the highly targeted transcriptional changes of sulphur metabolism genes in the transcriptomes of these mutant plants. Studies have used CRISPR-Cas9 mediated genome editing to target multiple gene copies in the allotetraploid B. napus and B. carinata genome (Braatz et al, 2017;Okuzaki et al, 2018;Sun et al, 2018;Yang et al, 2017;Yang et al, 2018) (Kirchner et al, 2017) with few reported off-target effects. To date, the only use of RNA-mediated CRISPR-Cas9 genome editing in Brassica oleracea is that of the technique used here developed at the John Innes Centre and described in (Lawrenson et al, 2019;Lawrenson et al, 2015).…”
Section: Crispr-cas9 In Complex Genomes and Functional Redundancymentioning
confidence: 99%